EDITORIAL - Kadankavil, K. T. (Journal of Dharma, 1980)
The opposition and tension between modernity and tradition, reform and revival is a constantly recurring phenomenon in the history of world religions. The nineteenth and twentieth centuries witnesses a number of such conflicting movements in Hinduism in India. In religion and philosophy, as in her political development, India was passing through a new era in her history. The British domination and the need for a religious revival pressed the educated to come forward to retrieve what had been neglected in the religio-cultural heritage of India and to reform some of the traditional practices. This is certainly not the story of Hinduism alone; other religions also have gone through similar movements. Evidently this is not a contemporary phenomenon; it has been ever-present in the history of all religions.